IMPROVING THE DECISION SUPPORT SYSTEM FOR MANAGING FINANCIAL RISKS OF INVESTMENT ACTIVITIES OF OIL AND GAS COMPANIES - Фадєєва, Ірина; Витвицька, У.Я.; Пиріг, А.М. (SWorldJournal, 2024)
The article substantiates a theoretical and methodological approach to identification and management of financial risks of oil and gas companies` investment activities, based on the use of IT, knowledge base and precedents. There is proposed a mathematica